The distributional impact of macroeconomic shocks in Mexico: threshold effects in a multi-region CGE model - Harris, Rebecca Lee (International Food Policy Research Institute, 1999)
This paper presents a regionally disaggregated computable general equilibrium (CGE) model of Mexico in order to examine the differential effects of external shocks across the regions. The model demonstrates how the internal migration regime is affected by exogenous changes in the presence of threshold effects, in which an exogenous change may not effect regional behavior until the shocks are large enough to overcome the isolation of local markets. The results show that migration helps mitigate the income changes caused by the simulations.